The perception of biotechnology in agro-forestry: The opinion of undergraduates and researchers. (July 2017) - Raparelli, Elisabetta; Bajocco, Sofia; Mugnozza, Giuseppe Scarascia
Graphical abstract: Abstract: Genetically modified organisms (GMOs) cropping promoted by different researchers, and the subsequent crisis regarding the safety of food derived from them, has resulted in strong public mistrust towards the authorities, both scientific and political. The aim of this work is to investigate the perception of Italian undergraduates and researchers towards the introduction of GMOs in agro-forestry. The factors determining attitudes towards GMOs were examined by means of 66 questions divided into three units: Knowledge, Opinon, Trust. Anagrafic and socio-cultural information were also analyzed. Data was processed through a multivariate analysis approach. The hierarchical clustering on undergraduates and researchers allowed to distinguish clusters of respondents skilled in biotechnology from those skilled in off-topic disciplines. Principal component analysis and K-means demonstrated that the positive or negative opinion toward GMOs, as for undergraduates, does not depend on their knowledge, but it is associated with the level of trust in the institutions. On the contrary, for researchers, it is related to their expertise level, without any linkage to trust in the institutions. This type of study may represent a key step for understanding the social, economic and scientific components underlying the choices of citizens, communities and society about GMOs.